Strategy to improve operational performance through organizational capacity, internal process management and innovation with digitalization operations as an intervening variable (Case Study on PT. Juan Sinergi Abadi) - Zaenal; Mombang Sihite; Lola Fitria Sari (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Digital transformation is a strategic need for project-based service companies, including interior contractors, to increase efficiency and competitiveness. However, the success of digitalization does not only depend on technology, but also on the organization's internal readiness. This research aims to analyze the role of organizational capacity, internal process management, and innovation in improving operational performance through digitalization at PT. Juan Sinergi Abadi. The method used was a mixed method with a sequential explanatory design, starting with a quantitative analysis using SEM-PLS on 60 employees, then continued with a qualitative approach through FGD and SWOT, IFE-EFE, IE Matrix, and QSPM analysis. The results of the study show that organizational capacity, internal process management, and innovation are the main factors in encouraging the implementation of operational digitalization. This digitalization has been proven to improve operational performance, especially in project time efficiency, cost control, and quality of work results. Qualitative findings reinforce that digital integration is able to align organizational capabilities, work processes, and innovation more effectively. Strategically, the company is in a hold and maintain position with a focus on strengthening digital systems and standardizing processes. This research contributes to the development of strategic management and provides practical implications for improving operational performance based on integrated digitalization